Newspaper Framing of 2023 Fuel Subsidy Removal Policy in Nigeria (Journal of Management and Social Sciences, 2024)
The media is saddled with the responsibility of informing the public about government policies and decisions. It is the lens through which individual sees issues and events outside their immediate life space. Since people form their reality through the contribution of others, the media through frame influences the way audience determine their social and political environment, by shaping their views and opinions. Framing theory provided the theoretical framework for this study while quantitative content analysis research design was adopted. Three national newspapers (The Punch, The Guardian and Daily Trust) were purposively selected for content analysis. Findings show episodic 72.5% as the dominant frame type used in reporting the 2023 fuel subsidy removal policy in Nigeria. Also, human interest 40%, attribution of responsibility 15%, and morality 15% frame typologies were mostly adopted. In addition, the selected newspapers gathered majority of their contents from the government 37.5% and their own media correspondence 22.5%. Findings further reveal news story format 72.5% and positive tone 55.0% as the dominant editorial format and tone respectively. It was inferred that the Nigerian media through frames types, typologies, news sources, editorial formats, and tone downplays the complexities of fuel subsidy removal policy. This may suggest that the media in Nigeria are strong instruments in the hands of the government as they often represent government policies as important, necessary and inevitable even when such policies bring hardship on the masses. Keywords Newspaper framing, fuel subsidy removal policy in Nigeria, Nigerian newspapers, Framing theory